Butterfly yellow - Lại, Thanhhà (University of Queensland Press, 2020)
A Vietnam War refugee in Texas partners with a city boy with rodeo dreams to track down the younger brother she was separated from six years before when he was evacuated by American troops during the waning days of the Vietnam War.